Poverty in American Higher Education - Katharine Broton (Journal of Postsecondary Student Success, 2021)
A substantial share of college students experience housing insecurity and too many students leave higher education before earning a credential. Both of these experiences are more common among students from low-income families who often lack adequate resources. While prior conceptual and qualitative investigations suggest that housing insecurity is associated with poorer student outcomes, this relationship has not been tested due to quantitative data limitations. In this paper, I use data from a state-wide longitudinal study of students from low-income families to conduct the first empirical test of the relationship between housing insecurity early in college and later college achievement and attainment. Findings show that housing insecurity is a statistically significant predictor of academic success, net of background factors. Specifically, housing insecurity is associated with an 8 to 12 percentage-point reduction in the probability of later degree attainment or enrollment. In the short-term, housing insecurity is also associated with lower mean GPA, a lower probability of obtaining at least a 2.0 GPA, and a higher probability of enrolling part-time rather than full-time, indicating that housing insecurity affects students’ college academic experiences in multiple ways. Efforts to promote college attainment should be expanded to consider students’ housing security. There are likely several points in time and multiple ways that higher education institutions, nonprofit agencies, and policymakers can intervene to promote secure housing and college success.